Strategic tropical natural resources management and household socio-economic resilience due to the Covid-19 pandemic - Cahyono, S. Andy; Agus, Cahyono; Raharjo, S. Agung Sri; Nugroho, Agung Wahyu; Indrajaya, Yonky (Academic Press, 2022)
Indonesia has a strategic role in geographical, political, economic, socio-cultural, defense, and international security strata. Indonesia has a tropical ecosystem with an abundance of natural resources, flora, fauna, ethnic diversity, mega-diversity, and natural beauty. Development and economic growth are multiplying but are still based on resource-based development. The Covid-19 pandemic caused a world economic recession, as economic growth declined sharply; unemployment increases, exports decline, investment decreases, purchasing power decreases, poverty, and economic uncertainty. Developing and emerging countries with weak access to technology and health have been particularly affected. All sectors of the Indonesian economy experienced a decline, except for the agricultural industry, which grew slightly positive. This paper discusses the role of an integrated bio-cycle system in household socio-economic resilience and management of tropical natural resources in the Covid and post-Covid era. Covid-19 has changed our thinking from resource extraction to resource efficiency, technological innovation, e-commerce, zero waste, and product safety. Food commodities, frozen food, biopharmaceuticals, non-timber forest products, and immune-enhancing foods have increased in demand during the Covid-19 pandemic, followed by changes in consumption, production, and distribution patterns. The pandemic has resulted in a relaxation of pressure on the earth's environment because almost all business, industrial, school, government, social, and transportation activities are locked down. Tropical ecosystems can be rapidly recovering and healing because they are supported by high rainfall, temperature, humidity, and organic cycles throughout the year. A new paradigm of knowledge-based development through the empowerment of natural resources must be developed more innovative, more global, more focused, and more futuristic for sustainable development after the Covid-19 era. Household economic resilience with an integrated bio-cycle system can withstand Covid-19. Management of land and living resources based on natural nature is intended to harmonize added value to the environment, economic, socio-cultural, and health aspects. This integrated farming system has a multi-functional and multi-product that is conservative productive to change consumer behavior and technology disruption. © 2023 Elsevier Inc. All rights reserved.